Fiscal Implications of the Global Economic and Financial Crisis. (IMF Staff Position Notes; Staff Position Note, 2009)
This note reflects macroeconomic and fiscal forecasts presented with the April 2009 World Economic Outlook, as well as information on fiscal stimulus and financial and industrial sector support gathered through mid-May. It follows the request by G-20 leaders for the Fund to assess regularly the actions taken by countries to address the global crisis and accelerate the recovery.